To solve the equation \(3(x - 4) = 18\), we start with the proposed method of first dividing by 3 and then adding 4.
If we divide both sides by 3: \[ x - 4 = 6 \] Then, adding 4 gives: \[ x = 10 \]
Now, let's examine the other methods listed:
-
First, distribute the 3, then add 12, and lastly divide by 3.
- Distributing gives \(3x - 12 = 18\).
- Adding 12 results in \(3x = 30\).
- Dividing by 3 gives \(x = 10\). (This method works.)
-
First, multiply by \( \frac{1}{3} \), then subtract 4.
- Multiplying by \( \frac{1}{3} \) gives \(x - 4 = 6\).
- Subtracting 4 gives \(x = 6 + 4\), which results in \(x = 10\). (This method works.)
-
First, distribute the 3, then add 4, and lastly divide by 3.
- Distributing gives \(3x - 12 = 18\).
- Adding 4 results in \(3x - 8 = 18\).
- Dividing by 3 gives \(x - \frac{8}{3} = 6\), which does not lead to the correct answer. (This method does not work.)
-
First, divide by 3, then subtract 4.
- Dividing by 3 gives \(x - 4 = 6\).
- Subtracting 4 gives \(x = 6 + 4\), which leads to \(x = 10\). (This method works.)
Therefore, the methods that result in the correct answer are:
- First, distribute the 3, then add 12, and lastly divide by 3.
- First, multiply by \( \frac{1}{3} \), then subtract 4.
- First, divide by 3, then subtract 4.
The only method listed that decently does lead us to the correct solution, as indicated, is the first option.